PELAKSANAAN KONSELING BAGI PECANDU NARKOBA DI BADAN NARKOTIKA NASIONAL KABUPATEN TAPANULI SELATAN - Hidayat, Arifin (UIN Sunan Kalijaga Yogyakarta, 2023)
Abuse of drug use is increasingly widespread, ranging from children, adolescents, adults, to the elderly. Users of various academic circles, politicians, artists (public vigur), and even students also use drugs. According to data released by BNN until March 2021, the Covid-19 situation also confiscated 3,462.75 kg of cannabis evidence, an increase of 143.64 percent compared to 2,419 kg of evidence in 2020. Even President Jokowi Dodo mentioned drug dealers and users. sentenced to death, but it turns out that there are still many people who consume drugs. This condition is very worrying and requires alternative solutions to change the behavior of drug addicts, BNN as one of the official state institutions in charge of dealing with drugs, it is important to make its best efforts, one of which is through counseling. This study wanted to describe the counseling process at the BNN in South Tapanuli Regency for drug addicts. Furthermore, this study uses a descriptive qualitative approach to the field. As for the results of the research, that BNN carried out the counseling process through the stages of assessment, planning, implementation, evaluation, and follow-up. However, there are still several obstacles, including: the introverted nature of the counselee, indiscipline, self-awareness, the counselor's academic ability, facilities and so on. So far, South Tapanuli BNNK has managed to cure 25 of 75 drug addicts. While those who have not recovered are still in the process of rehabilitation. As for the results of the research, that BNN carried out the counseling process through the stages of assessment, planning, implementation, evaluation, and follow-up. However, there are still several obstacles, including: the introverted nature of the counselee, indiscipline, self-awareness, the counselor's academic ability, facilities and so on. So far, South Tapanuli BNNK has managed to cure 25 of 75 drug addicts. While those who have not recovered are still in the process of rehabilitation. As for the results of the research, that BNN carried out the counseling process through the stages of assessment, planning, implementation, evaluation, and follow-up. However, there are still several obstacles, including: the introverted nature of the counselee, indiscipline, self-awareness, the counselor's academic ability, facilities and so on. So far, South Tapanuli BNNK has managed to cure 25 of 75 drug addicts. While those who have not recovered are still in the process of rehabilitation. South Tapanuli BNNK has successfully cured 25 of 75 drug addicts. While those who have not recovered are still in the process of rehabilitation. South Tapanuli BNNK has successfully cured 25 of 75 drug addicts. While those who have not recovered are still in the process of rehabilitation. Keywords: Counseling, Drug Addict, Behavioral Counseling